LIQUIDITY RISK DETERMINANTS: A COMPARATIVE STUDY OF ISLAMIC AND CONVENTIONAL BANKS IN SAUDI ARABIA - Yasmeen Diab Suleiman; Shabir Hakim (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
Both Islamic and conventional banks are exposed to the liquidity risk on asset side as well as liability side and management of the liquidity risk is indispensable for their smooth functioning and survival. This study identified seven internal (bank specific) and three external (macroeconomic) determinants of the liquidity risk and investigated their behavior in Islamic and conventional banks. Ten year data, from 2008 to 2017, of three Islamic banks and eight conventional banks operating in Saudi Arabia was used in panel at three levels: all banks, Islamic banks, and conventional banks. Generalize method of moments was applied to the estimation of the effect of the selected determinants on the liquidity risk. The test results of the model of this study show varied behavior of the determinants of liquidity in three datasets. In the composite of all banks, four factors: size, capital adequacy, earning assets and inflation were significant, with size having a negative relationship with the liquidity risk. In case of Islamic banks, two factors, size and inflation; size related positivity while inflation related negatively with the liquidity risk. The test results of the conventional banks reveal that five factors, return on assets, size, return on equity, earning assets, and inflation were significant. Among these, size had negative relationship with liquidity risk. Furthermore, the liquidity position of the conventional banks was observed to be better than that of the Islamic banks. These findings of this study shall be helpful for the banks in Saudi Arabia in understanding the sources of the liquidity risk and managing it properly. The investors can also the findings of this study in making well-informed investment decisions.